Effectiveness of Instructional Intervention on Medical and Health Information of Patients with Diabetes Mellitus Type II - abed, Rajaa; Yusif, Haleema (Iraqi National Journal of Nursing Specialties, 2014)
Objective: The objectives of the present study were to evaluate the effectiveness of the instructional interventionabout medical and health knowledge of patients with diabetes mellitus type II.Methodology: A Quasi- experimental study was carried out in National Center for Diabetes Mellitus/ AlmustansriaUniversity, started from 4th January 2012, to 1st April 2012. Non-probability (purposive sample) of (50) diabetesmellitus type II, who visit National Center for Diabetes Mellitus/ Almustansria University. The study sample isdivided equally into (25) study and (25) control groups. The study group received the instructional intervention.While the control not exposed to the instructional intervention. The data are collected through the use ofconstructed questionnaire, which consists of two parts. Part 1: consists of demographic characteristics. Part 2consists of (13) items about medical knowledge and health of patients with diabetes mellitus type II.Results: The findings of the study indicated that the patient’s medical knowledge and health is low and poorbefore the implementation of the instructional intervention but after the implementation of the instructionalintervention the medical knowledge and health of diabetes mellitus type II greatly improved.Recommendations: The study recommended that that the diabetes centers in Iraq should include instructionalintervention about medical knowledge and health of diabetes mellitus type II to increase awareness of diabeticpatients regarding knowledge for diabetes mellitus type II